Multidimensional Inventory for Religious Spiritual Well-Being (MI RSWB 48): Validation with Iranian psychiatric outpatients. Issue 10 (26th November 2019) - Kazemzadeh Atoofi, Mehrdad; Dadfar, Mahboubeh; Turan, Yahya; Behnam, Leila
ABSTRACT: The aim of this study was to investigate the validation of the Multidimensional Inventory for Religious Spiritual Well-Being (MI RSWB 48) in a convenience sample of 250 Iranian psychiatric outpatients. In addition to the MI RSWB 48, the patients completed the Spiritual Well-Being Scale (SWS), the WHO-5, the PHQ-9, and the PHQ-15. Cronbach's α for the MI RSWB 48 was .84, and for its subscales ranged from .33 (Hope Transcendent [HT] Subscale) to .89 (General Religiosity [GR] Subscale). The SWS score had the highest positive correlation with the MI RSWB 48 score. Two factors identified for the scale. The religiosity spirituality score of female patients was significantly higher than the score of the male patients. The MI RSWB 48 can be considered as a suitable tool for evaluating different aspects of religiosity and spirituality in Iranian society. The HT Subscale may need modification to improve its internal consistency.